2001
DOI: 10.1111/j.0014-3820.2001.tb01324.x
|View full text |Cite
|
Sign up to set email alerts
|

Albinism and Phenotype of Barn Swallows (Hirundo Rustica) From Chernobyl

Abstract: Abstract. The effects of mutation on phenotypic expression are supposed to be mainly deleterious because mutations disrupt the expression of genes that function relatively well under current environmental conditions. Thus, mutations are assumed to give rise to deviant phenotypes that are generally selected against. Radioactive contamination in the Chernobyl region of Ukraine is associated with a significant increase by a factor two to 10 in mutation rate in microsatellite markers of the barn swallow, Hirundo r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
47
0
11

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 33 publications
(45 reference statements)
2
47
0
11
Order By: Relevance
“…Previous studies on the barn swallow in the Ukraine have found that birds in areas with elevated radiation around Chernobyl have more pale melanin-based plumage pigmentation than in control areas, in particular long-tailed males (Camplani et al 1999). In addition, 87 out of the 88 partial albinos caused by mutation had partly albinistic feathers within the red melanin-based plumage, whereas only nine were expected, given the area of the red plumage badge (Møller & Mousseau 2001), suggesting that partial albinism is directly related to this melanin-based coloration. Adult barn swallow males with long tails tend to have a more strongly reflecting red throat plumage colour than do short-tailed males, and such birds also have higher levels of circulating carotenoids in the blood .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies on the barn swallow in the Ukraine have found that birds in areas with elevated radiation around Chernobyl have more pale melanin-based plumage pigmentation than in control areas, in particular long-tailed males (Camplani et al 1999). In addition, 87 out of the 88 partial albinos caused by mutation had partly albinistic feathers within the red melanin-based plumage, whereas only nine were expected, given the area of the red plumage badge (Møller & Mousseau 2001), suggesting that partial albinism is directly related to this melanin-based coloration. Adult barn swallow males with long tails tend to have a more strongly reflecting red throat plumage colour than do short-tailed males, and such birds also have higher levels of circulating carotenoids in the blood .…”
Section: Introductionmentioning
confidence: 98%
“…Radiation has been proposed to reduce levels of antioxidants that are used for DNA repair because antioxidants are used for removing free radicals that arise owing to radiation (Ben-Amotz et al 1998;Ivaniota et al 1998;Neyfakh et al 1998a,b;Kumerova et al 2000). It has been suggested that this reduction in antioxidants may be responsible for increased levels of mutation in radioactively contaminated areas, such as those around Chernobyl in Ukraine (Dubrova et al 1996;Ellegren et al 1997;Kovalchuk et al 2000;Møller & Mousseau 2001). This increase in mutations may arise from the direct effects of radiation or indirectly through the effects of a reduction in levels of antioxidants on levels of mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Ellegren et al (1997) reported an increase in germline mutation rates in barn swallow microsatellite DNA by a factor of two to 10 when comparing families from Kanev with families from Chernobyl. Barn swallows from Chernobyl have markedly increased frequency of partial albinism in the plumage (Ellegren et al 1997;Møller and Mousseau 2001). Previous studies have shown significant parent-offspring resemblance in partial albinism, indicating that such albinism is partly of germline origin (Ellegren et al 1997).…”
mentioning
confidence: 99%
“…La coloración atípica en el plumaje de aves silvestres es poco frecuente (Jehl 1985), puede originarse por mutaciones genéticas (van Grouw 2006) y potencialmente se expresan bajo condiciones ambientales alteradas (Phillips 1954, Buckley 1982, Møller & Mousseau 2001. Estas aberraciones se catalogan con base en el grado de pigmentación como ausencia, reducción o exceso de melaninas (Davis 2007).…”
unclassified
“…Sin embargo, en México, se observa una marcada relación entre los casos de anomalías cromáti-cas en áreas alteradas antropogénicamente (López-Ortega & Carbó-Ramírez 2010, Tinajero & Rodríguez-Estrella 2010, Carbó-Ramírez et al 2011, Contreras & Ruiz 2011, Rodríguez-Ruiz et al 2014, Ayala-Pérez et al 2014, Cortinas-Salazar & Contreras-Balderas 2014, lo cual muestra una tendencia creciente en la probabilidad de registrar individuos con plumajes de coloraciones aberrantes (Nemésio 2001, Møller & Mousseau 2001, posiblemente por el estrés ambiental que ocasionan diversas actividades humanas (urbanización, agricultura y ganadería; Rodríguez-Ruiz et al 2014).…”
unclassified